A recurrent fusion gene in high-grade endometrial stromal sarcoma: a new tool for diagnosis and therapy? - Ried, Thomas; Gaiser, Timo (Genome medicine, 2012)
High-grade endometrial stromal sarcomas (ESSs) are an aggressive group of endometrial stromal tumors. A recent study described a recurrent chromosomal translocation (t(10;17)) occurring in ESS, which joins the gene 14-3-3ε with either FAM22A or FAM22B. Expression of the resulting fusion gene leads to malignant transformation, and silencing of its expression reverses the malignant phenotype. Because the fusion can be readily detected in diagnostic samples using fluorescent in situ hybridization, this chromosomal aberration could be used to differentiate high-grade ESS from the low-grade, less aggressive form. Discovery of the new oncoprotein could also provide entry points for targeted therapies.
Gesehen am 22.08.2018